Optimizing outcomes in ulnar nerve injuries: nerve grafting after primary neurorrhaphy - Garzón Ortega, Victor Hugo; Hernández Barrón, Verania Fernanda; Varela Gómez, Fernando Fernández; Santos Moyron, Lucio Alejandro; Cárdenas Mejía, Alexander (International Surgery Journal, 2025)
This case series rigorously assesses the efficacy of primary neurorrhaphy followed by secondary nerve grafting in five patients with ulnar nerve injuries, utilizing the quick disabilities of the arm, shoulder, and hand (QuickDASH) score as a standardized measure of functional outcomes. Treated between 2019 and 2023, these patients underwent initial neurorrhaphy followed by nerve transfer. Functional assessments were conducted preoperatively, post-neurorrhaphy, and post-nerve transfer using the QuickDASH questionnaire. The mean preoperative QuickDASH score was 43.00 (standard deviation [SD]=7.34), improving to 36.20 (SD=6.54) after neurorrhaphy (mean difference=-6.8, p<0.01), and further to 24.20 (SD=2.59) after nerve transfer (mean difference=-12, p<0.01). Paired t-tests substantiated statistically significant enhancements in functional activity at each intervention stage (p<0.01). These results indicate that integrating primary neurorrhaphy with secondary nerve transfer effectively restores nerve function in acute ulnar nerve lacerations. This study underscores the potential of these combined surgical strategies to optimize outcomes in complex peripheral nerve injuries, though larger-scale investigations are warranted to confirm these findings.